Fundus Fluorescein Angiography (FFA) in Human Subjects Displays Circadian Variation - Hopkins, Alan (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2021)
The relationship between retinal inner blood-retina barrier (iBRB) permeability, the circadian clock and their possible role in retinal pathology is unknown. We performed quantitative fundus fluorescein angiography (FFA) in the morning and evening in healthy human subjects aged 18 - 30 years old to assess for any changes in retinal vascular integrity. 15 volunteers were recruited, and informed consent was obtained from all participants (Appendices i & ii). Fundus colour photography, optical coherence tomography (OCT) and FFA were performed at a defined time in the morning and again in the evening, with a minimum of 48 hours between each investigation, to allow for washout of fluorescein before retesting. The chronotype of each person was determined using the Munich Chronotype Questionnaire (MCTQ). Volunteers were excluded if they had any pre-defined medical or ophthalmic history, as outlined in our ethical approval documentation. Sodium fluorescein (500 mcg), followed by a 5mL flush of 0.9% sodium chloride, was injected via a peripheral cannulation site from which blood was also initially drawn for later analysis. FFA images of the posterior pole were captured every 15 s from completion of the infusion to 10 min. Fundal images were later independently reviewed by a consultant ophthalmologist and ImageJ analysis was used for quantification of OCT and FFA images. The macula was divided into 3 regions for analysis, based on the Early Treatment Diabetic Retinopathy Study grid, comprising the central fovea, inner macula and outer macula.? Fluorescein signal was evident and more prolonged in the evening compared to the morning in the same subject and this was significantly increased in all macular regions analysed (n = 15 subjects, ***P < 0.001). There were no significant OCT in any measured parameters, including central foveal thickness, between the time points. Cortisol levels were in line with expected normal physiology. Increased cortisol levels were measured in the morning. This supports that analysis of the MCTQ achieved the correct times to test each volunteer with regards to their circadian cycle. We have shown that there is a significant increase and more prolonged fluorescein signal in the evening compared to the morning in healthy volunteers. This indicates a systemically injected tracer molecule in human subjects undergoes a potential size-selective passive diffusion from the inner retinal vasculature to the retinal parenchyma with diffusion towards the outer retina and retinal pigment epithelium (RPE). An inner retina derived supply of systemic components to the photoreceptor outer segments and RPE has not been described previously and may represent a critically important physiological process central to the development of a range of retinopathies, including age-related macular degeneration (AMD). Previous non-human work from our lab indicates that a tight junction molecule, Claudin-5, whose expression varies with the circadian rhythm, plays a key role in the cycling of the iBRB permeability. The results of this current study are discussed in tandem with previous work, and for added clinical relevance, also in the setting of the pathophysiology of AMD.
APPROVED